2D Linear Trap Array for Quantum Information Processing. Issue 11 (16th September 2020) - Holz, Philip C.; Auchter, Silke; Stocker, Gerald; Valentini, Marco; Lakhmanskiy, Kirill; Rössler, Clemens; Stampfer, Paul; Sgouridis, Sokratis; Aschauer, Elmar; Colombe, Yves; Blatt, Rainer
Abstract: An ion‐lattice quantum processor based on a two‐dimensional arrangement of linear surface traps is presented. The design features a tunable coupling between ions in adjacent lattice sites and a configurable ion‐lattice connectivity, allowing one, for example, to realize rectangular and triangular lattices with the same trap chip. Detailed trap simulations of a simplest‐instance ion array with 2 × 9 trapping sites are presented and the fabrication of a prototype device in an industrial facility is reported on. The design and the employed fabrication processes are scalable to larger array sizes. Trapping of ions in rectangular and triangular lattices and transport of a 2 × 2 ion‐lattice over one lattice period are demonstrated. Abstract : A scalable ion‐lattice quantum processor is proposed, employing a two‐dimensional arrangement of linear surface ion traps to confine ion qubits on a 2D lattice. Tunable site‐to‐site coupling and configurable lattice connectivity extend the options for emulating 2D spin systems. Design, fabrication, and commissioning of a prototype processor are described, and strategies are discussed to scale‐up the device.